Nigeria-IMF Relationship and Its Impact on Human Rights and Standard of Living in Nigeria - Raziqa Muhammad Shafiu; Mohd Afandi Salleh (Yustisia, 2021)
This study examines the relationship between Nigeria and the International Monetary Fund (IMF) and also traces its impact on Human Rights and Standard of living. Therefore, it assesses the impact of IMF on Human Rights and the living standards of Nigerians, as it was assumed that Nigeria's relationship with the IMF was the key cause of poverty, social insecurity, economic inequalities and a decrease in people's living standards. Primary data sources, such as official records, newspapers, journals, and books, were used to gather data for research, while the Theory of Human Rights and Dependency Theory was used as the basis for this study. The study discovered that externally enforced economic liberalization does not enhance economic development and degrades government human rights practices. The study also assumed that Nigeria's relationship with the IMF was more detrimental than positive and thus had a direct negative impact on the general standard of living of the people. It was suggested that the government should attempt to diversify the economy, reshape its relationship with international financial institutions, such as the IMF and the World Bank, and provide people with adequate facilities to raise their living standards.